Răspuns :
[tex]a)\left\{\begin{matrix}
x = 2\\
3x - 5y = 1\end{matrix}\right.[/tex]
[tex]3x - 5y = 1[/tex]
[tex]3 \times 2 - 5y = 1[/tex]
[tex]6 - 5y = 1[/tex]
[tex] - 5y = 1 - 6[/tex]
[tex] - 5y = - 5 \: | \div ( - 5)[/tex]
[tex]y = 1[/tex]
[tex]b)\left\{\begin{matrix}
y = - 1\\
- 2x - 4y = 0\end{matrix}\right.[/tex]
[tex] - 2x - 4y = 0[/tex]
[tex] - 2x - 4 \times ( - 1) = 0[/tex]
[tex] - 2x + 4 = 0[/tex]
[tex] - 2x = - 4 \: | \div ( - 2)[/tex]
[tex]x = 2[/tex]
[tex]c)\left\{\begin{matrix}
x + y = 5\\
x - y = - 1\end{matrix}\right.[/tex]
[tex]x + y = 5[/tex]
[tex]x = 5 - y[/tex]
[tex]x - y = - 1[/tex]
[tex]5 - y - y = - 1[/tex]
[tex] - y - y = - 1 - 5[/tex]
[tex] - 2y = - 6 \: | \div ( - 2)[/tex]
[tex]y = 3[/tex]
[tex]x + y = 5[/tex]
[tex]x + 3 = 5[/tex]
[tex]x = 5 - 3[/tex]
[tex]x = 2[/tex]
[tex]d)\left\{\begin{matrix}
- x - 5y = 4\\
3x - 2y = 5\end{matrix}\right.[/tex]
[tex] - x - 5y = 4[/tex]
[tex] - x = 4 + 5y \: | \times ( - 1)[/tex]
[tex]x = - 4 - 5y[/tex]
[tex]3x - 2y = 5[/tex]
[tex]3( - 4 - 5y) - 2y = 5[/tex]
[tex] - 12 - 15y - 2y = 5[/tex]
[tex] - 15y - 2y = 5 + 12[/tex]
[tex] - 17y = 17 \: | \div ( - 17)[/tex]
[tex]y = - 1[/tex]
[tex]x = - 4 - 5y[/tex]
[tex]x = - 4 - 5 \times ( - 1)[/tex]
[tex]x = - 4 + 5[/tex]
[tex]x = 1[/tex]
[tex]e)\left\{\begin{matrix}
3x - 5y = - 4\\
6x - 2y = 8 \: | \div 2 \end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
3x - 5y = - 4\\
3x - y = 4\end{matrix}\right.[/tex]
[tex]3x - y = 4[/tex]
[tex] - y = 4 - 3x \: | \times ( - 1)[/tex]
[tex]y = 3x - 4[/tex]
[tex]3x - 5y = - 4[/tex]
[tex]3x - 5(3x - 4) = - 4[/tex]
[tex]3x - 15x + 20 = - 4[/tex]
[tex]3x - 15x = - 4 - 20[/tex]
[tex] - 12x = - 24 \: | \div ( - 12)[/tex]
[tex]x = 2[/tex]
[tex]y = 3x - 4[/tex]
[tex]y = 3 \times 2 - 4[/tex]
[tex]y = 6 - 4[/tex]
[tex]y = 2[/tex]
[tex]f)\left\{\begin{matrix}
2x + 5y = 1\\
3x + 10y = - 1\end{matrix}\right.[/tex]
[tex]2x + 5y = 1[/tex]
[tex]2x = 1 - 5y[/tex]
[tex]x = \frac{1 - 5y}{2} [/tex]
[tex]3x + 10y = - 1[/tex]
[tex]3 \times \frac{1 - 5y}{2} + 10y = - 1[/tex]
[tex] \frac{3(1 - 5y)}{2} + 10y = - 1[/tex]
[tex] \frac{3 - 15y}{2} + 10y = - 1 \: | \times 2[/tex]
[tex]3 - 15y + 20y= - 2[/tex]
[tex] - 15y + 20y = - 2 - 3[/tex]
[tex]5y = - 5 \: | \div 5[/tex]
[tex]y = - 1[/tex]
[tex]x = \frac{1 - 5y}{2} [/tex]
[tex]x = \frac{1 - 5 \times ( - 1)}{2} [/tex]
[tex]x = \frac{1 + 5}{2} [/tex]
[tex]x = \frac{6}{2} [/tex]
[tex]x = 3[/tex]
x = 2\\
3x - 5y = 1\end{matrix}\right.[/tex]
[tex]3x - 5y = 1[/tex]
[tex]3 \times 2 - 5y = 1[/tex]
[tex]6 - 5y = 1[/tex]
[tex] - 5y = 1 - 6[/tex]
[tex] - 5y = - 5 \: | \div ( - 5)[/tex]
[tex]y = 1[/tex]
[tex]b)\left\{\begin{matrix}
y = - 1\\
- 2x - 4y = 0\end{matrix}\right.[/tex]
[tex] - 2x - 4y = 0[/tex]
[tex] - 2x - 4 \times ( - 1) = 0[/tex]
[tex] - 2x + 4 = 0[/tex]
[tex] - 2x = - 4 \: | \div ( - 2)[/tex]
[tex]x = 2[/tex]
[tex]c)\left\{\begin{matrix}
x + y = 5\\
x - y = - 1\end{matrix}\right.[/tex]
[tex]x + y = 5[/tex]
[tex]x = 5 - y[/tex]
[tex]x - y = - 1[/tex]
[tex]5 - y - y = - 1[/tex]
[tex] - y - y = - 1 - 5[/tex]
[tex] - 2y = - 6 \: | \div ( - 2)[/tex]
[tex]y = 3[/tex]
[tex]x + y = 5[/tex]
[tex]x + 3 = 5[/tex]
[tex]x = 5 - 3[/tex]
[tex]x = 2[/tex]
[tex]d)\left\{\begin{matrix}
- x - 5y = 4\\
3x - 2y = 5\end{matrix}\right.[/tex]
[tex] - x - 5y = 4[/tex]
[tex] - x = 4 + 5y \: | \times ( - 1)[/tex]
[tex]x = - 4 - 5y[/tex]
[tex]3x - 2y = 5[/tex]
[tex]3( - 4 - 5y) - 2y = 5[/tex]
[tex] - 12 - 15y - 2y = 5[/tex]
[tex] - 15y - 2y = 5 + 12[/tex]
[tex] - 17y = 17 \: | \div ( - 17)[/tex]
[tex]y = - 1[/tex]
[tex]x = - 4 - 5y[/tex]
[tex]x = - 4 - 5 \times ( - 1)[/tex]
[tex]x = - 4 + 5[/tex]
[tex]x = 1[/tex]
[tex]e)\left\{\begin{matrix}
3x - 5y = - 4\\
6x - 2y = 8 \: | \div 2 \end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
3x - 5y = - 4\\
3x - y = 4\end{matrix}\right.[/tex]
[tex]3x - y = 4[/tex]
[tex] - y = 4 - 3x \: | \times ( - 1)[/tex]
[tex]y = 3x - 4[/tex]
[tex]3x - 5y = - 4[/tex]
[tex]3x - 5(3x - 4) = - 4[/tex]
[tex]3x - 15x + 20 = - 4[/tex]
[tex]3x - 15x = - 4 - 20[/tex]
[tex] - 12x = - 24 \: | \div ( - 12)[/tex]
[tex]x = 2[/tex]
[tex]y = 3x - 4[/tex]
[tex]y = 3 \times 2 - 4[/tex]
[tex]y = 6 - 4[/tex]
[tex]y = 2[/tex]
[tex]f)\left\{\begin{matrix}
2x + 5y = 1\\
3x + 10y = - 1\end{matrix}\right.[/tex]
[tex]2x + 5y = 1[/tex]
[tex]2x = 1 - 5y[/tex]
[tex]x = \frac{1 - 5y}{2} [/tex]
[tex]3x + 10y = - 1[/tex]
[tex]3 \times \frac{1 - 5y}{2} + 10y = - 1[/tex]
[tex] \frac{3(1 - 5y)}{2} + 10y = - 1[/tex]
[tex] \frac{3 - 15y}{2} + 10y = - 1 \: | \times 2[/tex]
[tex]3 - 15y + 20y= - 2[/tex]
[tex] - 15y + 20y = - 2 - 3[/tex]
[tex]5y = - 5 \: | \div 5[/tex]
[tex]y = - 1[/tex]
[tex]x = \frac{1 - 5y}{2} [/tex]
[tex]x = \frac{1 - 5 \times ( - 1)}{2} [/tex]
[tex]x = \frac{1 + 5}{2} [/tex]
[tex]x = \frac{6}{2} [/tex]
[tex]x = 3[/tex]